A Comprehensive Review of Smart Thermosensitive Nanocarriers for Precision Cancer Therapy - Yaramiri, Atena (2025)
By 2030, millions of new cancer cases will be diagnosed, as well as millions of cancer-related deaths. Traditional drug delivery methods have limitations, so developing smart drug delivery systems (SDDs) has emerged as a promising avenue for more effective and precise cancer treatment. Nanotechnology, particularly nanomedicine, provides innovative approaches to enhance drug delivery, including the use of nanoparticles. One such type of SDD is thermosensitive nanoparticles, which respond to internal and external stimuli, such as temperature changes, to release drugs precisely at tumor sites and minimize off-target effects. On the other hand, hyperthermia is a cancer treatment mode that goes back centuries and has become popular because it can target cancer cells while sparing healthy tissue. This paper presents a comprehensive review of smart thermosensitive nanoparticles for cancer treatment, with a primary focus on organic nanoparticles. The integration of hyperthermia with temperature-sensitive nanocarriers, such as micelles, hydrogels, dendrimers, liposomes, and solid lipid nanoparticles, offers a promising approach to improving the precision and efficacy of cancer therapy. By leveraging temperature as a controlled drug release mechanism, this review highlights the potential of these innovative systems to enhance treatment outcomes while minimizing adverse side effects.